The Extraterritorial Effect of Federal Criminal Statutes: Offenses Directed at Members of Congress - Petersen, Mark (1983)
In a world of increased tension and open hostility toward the United States and its policies, an attack or assault on a member of Congress traveling abroad is not inconceivable. Section 351 of the United States Criminal Code prescribes penalties for offenses directed at members of Congress including assault, killing, kidnapping, and attempted conspiracies. Section 351, however, is silent as to a court's reach in asserting subject matter jurisdiction. This Note addresses the issue of whether the United States federal courts could obtain jurisdiction over a foreign group or individual who attacked or killed a Congressperson in a foreign country. Emphasizing the jurisdictional principles of the law of nations, the author will conclude that a federal court would be justified in asserting subject matter jurisdiction over a foreign defendant who violated section 351 outside of the United States